AB0463 Clinical significance of antibodies to infliximad in rheumatoid arthritis (RA) patients. (23rd January 2014) - Lukina, G.; Sigidin, Y.; Alexandrova, E.; Novikov, A.; Aronova, E.; Kanonirova, M.; Glukhova, S.; Nasonov, E.
Abstract : Objectives: To assess efficacy and tolerability of infliximab (INF) in patients (pts) with RA depending on the presence of antibodies to INF (ATI) in the serum. Methods: Twenty-two pts with active RA despite methotrexate therapy (19 women, mean age 45, 8 years, mean disease duration 9, 2 years, RF-positive 17, mean CRP 22 mg/L, mean HAQ 1, 5, mean DAS28 6) were treated in one center with INF (3 mg/kg intravenously at weeks 0, 2, 6 and every 8 weeks thereafter). Pts were assessed by EULAR criteria at weeks 0, 14 and 22; ATI were measured by TNFα-Bloker-ADA ELISA kit (Immunodiagnostik AG, Germany) at the same points. Correlations between clinical results and the presence of ATI were analyzed. Results: Before INF treatment no pt had ATI. Twenty pts completed the study. By the 22-nd week ATI were detected in 7 pts. Among them good results were registered in 2 pts; moderate results, 2 pts; no effect, 3 pts. Thirteen pts had no serum ATI. In this group clinical effect was assessed as good in 5 pts, and as moderate in 8 pts. No poor effect was noted among these pts. Positive (good and moderate) results were achieved in pts without ATI significantly more often (p=0, 035). Frequency of adverse events was the same in both groups. Conclusions: Presence of ATI can be considered as a risk factor for the reduction of the INF clinical effect. Disclosure of Interest: None Declared